Society – Part 2 - Mises, Ludwig von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The author continues the analysis of the nature of society emphasizing the development of the division of labor and the changes it brings to the individual and social development. He differentiates the concepts of social evolution and social regression, showing how the latter happened in history when there was no social cooperation. The author concludes discussing the importance of private property for the vigorous development of society, while presenting opposing instincts to its development.